2020
DOI: 10.3390/rs12071168
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based CYGNSS Soil Moisture Estimates over ISMN sites in CONUS

Abstract: Soil moisture (SM) derived from satellite-based remote sensing measurements plays a vital role for understanding Earth’s land and near-surface atmosphere interactions. Bistatic Global Navigation Satellite System (GNSS) Reflectometry (GNSS-R) has emerged in recent years as a new domain of microwave remote sensing with great potential for SM retrievals, particularly at high spatio-temporal resolutions. In this work, a machine learning (ML)-based framework is presented for obtaining SM data products over the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…In particular, the compounding effects of surface roughness and topography could be significant over contributing areas within a spaceborne receiver's footprint while will generally be on the order of several hundreds of meters. While previous research has observed successful surface SM estimation from GNSS-R signals under a dominantly coherent signal assumption [33]- [35], the effects of topography and surface roughness deserve an in-depth analysis for these spatial scales [36]- [38]. Under a moderately smooth surface assumption (≈ 1.5 cm), coherent signals at L-band and lower will be minimally effected by surface roughness.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the compounding effects of surface roughness and topography could be significant over contributing areas within a spaceborne receiver's footprint while will generally be on the order of several hundreds of meters. While previous research has observed successful surface SM estimation from GNSS-R signals under a dominantly coherent signal assumption [33]- [35], the effects of topography and surface roughness deserve an in-depth analysis for these spatial scales [36]- [38]. Under a moderately smooth surface assumption (≈ 1.5 cm), coherent signals at L-band and lower will be minimally effected by surface roughness.…”
Section: Discussionmentioning
confidence: 93%
“…To achieve this, CYGNSS uses eight small satellites that orbit the tropics (within ±38 • latitudes). The considerable amount of CYGNSS land observation data also measured in this region has greatly contributed to the development of new SM retrieval approaches from spaceborne GNSS-R [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we apply a machine learning (ML) framework that is similar to those previously developed by [25,26] to perform SM predictions at a high spatio-temporal resolution. The framework uses in-situ SM data sets provided by the International Soil Moisture Network (ISMN) to train CYGNSS observations that fall within approximately 9 km × 9 km grid centering each ISMN site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is that the differences in estimator performance can lead to different results, and the I/F signal dataset used is too small, lacking sufficient persuasive power. Based on the different assumptions, several SM inversion methods have also been developed, such as spatial averaging, combine linear regression method, machine-learning method, and the global inversion accuracy of SM can reach about 0.05 cm 3 /cm 3 [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%